f(x)=3x-2

Simple and best practice solution for f(x)=3x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(x)=3x-2 equation:


Simplifying
f(x) = 3x + -2

Multiply f * x
fx = 3x + -2

Reorder the terms:
fx = -2 + 3x

Solving
fx = -2 + 3x

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Divide each side by 'x'.
f = -2x-1 + 3

Simplifying
f = -2x-1 + 3

Reorder the terms:
f = 3 + -2x-1

 

See similar equations:

| 25y^3+10y= | | (5-4i)(.1-i)=0 | | 602-67x=1 | | 15.1(x)=3x-2 | | -3(x+4)=3(-4-x) | | 6k+4-3k=2 | | 1.5(x)=3x-2 | | -1+7x=55 | | -x+10=-38+5x | | 40x^4-10x^2= | | 8+12s-7-9s+4= | | 10(x+6)=-6(x-2) | | 40/16=x | | 40x=120 | | Graphy=20-3x | | 3[3-5]-3=18 | | 10k-31=11k+76 | | 24x+2+25x=180 | | 6r-3t=6 | | 24x+2=25x | | -28=5x-7x-10 | | -4x+7y=15 | | X^5-4x^3-x^2+4=0 | | 3x-16=28+2x | | 12x+14+110=180 | | 4y+5-2y=8 | | -27y=1 | | 6-y=-87+2y | | 3[3-5r]-3=-18 | | 8(4q+-5)-7q=20q+-10 | | x-2(y-3)=0 | | 3+x=4x-6 | | 10+4x=-5x+64 | | 1/2x-4y=4 | | 10x+10=12x-4 | | 8=8-4(v-8) | | 857x+763=960x-636 | | 5n+10+8n-9n+3= | | 5x-8=4+2x | | x+4=-16 | | 1/3t=33 | | -4(6x-8)=12x+14 | | 6+6x=-4+6 | | 5(3x+1)^1/4=10 | | 3/5x+1/5y+1/5z=25 | | 6w^2=-24w | | -1-2(x+3)+2=1 | | u/6=8 | | 3b-98b=11 | | ((x+5)/(14))=(4/7)/((x-4)/8) | | 1-2(x+3)+2=1 | | 8e-9=3w+16 | | -7x-7=3x-77 | | -2(4+9w)= | | -3(x-1)=-2(-3+3x) | | 8+4x=4(x+2) | | -4-2n=-6(1+2n)+2 | | 15x-2=23x-25x | | X+3=-3x+7 | | 2x-(-16)=26 | | M-325=339 | | 6x+8=-6x+80 | | 12/0.75= | | 14x+7-20x+15=90 | | A=5+3(4-2) |